2020
DOI: 10.3390/ijms21083009
|View full text |Cite
|
Sign up to set email alerts
|

Human NANOS1 Represses Apoptosis by Downregulating Pro-Apoptotic Genes in the Male Germ Cell Line

Abstract: While two mouse NANOS paralogues, NANOS2 and NANOS3, are crucial for maintenance of germ cells by suppression of apoptosis, the mouse NANOS1 paralogue does not seem to regulate these processes. Previously, we described a human NANOS1 p.[(Pro34Thr);(Ser83del)] mutation associated with the absence of germ cells in seminiferous tubules of infertile patients, which might suggest an anti-apoptotic role of human NANOS1. In this study, we aimed to determine a potential influence of human NANOS1 on the maintenance of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Downregulation of this phase accelerates both cell proliferation and S phase [ 39 ]. These results are in line with our previous findings that NANOS1 downregulates GADD45 family members which are involved in G1/S phase DNA damage checkpoint [ 20 ]. In turn, in the case of NANOS3 overexpression, we observed a higher number of cells in the G2/M phase compared to control cells ( Figure 3 B bottom panel).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Downregulation of this phase accelerates both cell proliferation and S phase [ 39 ]. These results are in line with our previous findings that NANOS1 downregulates GADD45 family members which are involved in G1/S phase DNA damage checkpoint [ 20 ]. In turn, in the case of NANOS3 overexpression, we observed a higher number of cells in the G2/M phase compared to control cells ( Figure 3 B bottom panel).…”
Section: Resultssupporting
confidence: 93%
“…Namely, a mutation of NANOS1 is associated with male infertility caused by absence of germ cells in the seminiferous tubules of patients [ 19 ]. Moreover, when this NANOS1 gene mutation was tested in a hPGCs model, TCam-2 cell line, it resulted in a functional switch of NANOS1 from anti-apoptotic to pro-apoptotic, providing an explanation of the infertility phenotype of the patients [ 20 ]. In turn, NANOS3 gene mutations were found to be associated with premature ovarian insufficiency, a female infertility phenotype [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it demonstrated that NANOS1 caused a significant decrease in apoptosis. It was further demonstrated by transcriptomic data that the NANOS1-mediated decrease in apoptosis was accompanied by the downregulation of pro-apoptotic genes such as RHOB , MYC , and GADD45 family genes [ 26 ]. These genes are downstream targets of p53 and are involved in p53-mediated DNA-damage checkpoint pathway.…”
Section: Nanos1 In Cancermentioning
confidence: 99%
“…With the emergence of multiple Nanos paralogues during evolution, mammalian Nanos paralogues (Nanos1, Nanos2, and Nanos3) diverged in their functions and adopted distinct roles in germline development. For example, NANOS1 represses apoptosis in human germ cell line TCam-2 [ 26 ], while mouse Nanos2 is crucial for inducing mitotic arrest during male germ cell development [ 27 ]. Lastly, Nanos3 is important for the maintenance of the male germline stem cells [ 28 ] and suppresses premature spermatogonial differentiation [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The nanos gene family codes for zinc-finger containing RNA-binding proteins, with apoptosis and differentiation promoting mRNA targets, thereby inhibiting those processes (21,22). The activity of both gene families is especially conserved in the germline of vertebrates and insects, where they ensure genomic integrity and keep gametes in a stem cell-like state (23)(24)(25)(26). In Nematostella, we found three piwi genes (one of which appears to be a pseudogene) (27) and two nanos paralogs, nanos1 and nanos2.…”
Section: Introductionmentioning
confidence: 99%